[The Glad Tidings of the conquest of Islamicjerusalem in the context of Sura Rum; The symbolic (Ishari) exegesis of Ibn Barrajan]RÛM SÛRESİ ÇERÇEVESİNDE BEYTÜLMAKDİS'İN FETHİNİN MÜJDELENMESİ -İbn Berrecân'ın İşârî Tefsir Yorumu-. (2015) - ARPA, Abdulmuttalip
No abstract available